Alvie eats soup - Collins, Ross. (New York : Arthur A. Levine Books, 2002)
Alvie will eat only soup, and his parents are worried that his Granny Fanny, a famous chef, will find out.
Keywords: Food habits -- Fiction; Soups -- Fiction; Grandmothers -- Fiction